Invariant based control of induction and maintenance phases for anesthesia. Issue 26 (2016) - Fiacchini, Mirko; Queinnec, Isabelle; Tarbouriech, Sophie; Mazerolles, Michel
Abstract: Set theory and invariant sets are the key ingredients used in this paper to address the control problem of general anesthesia. Both the induction phase, corresponding to the administration of an open-loop bolus dose, and the maintenance phase of the depth of hypnosis during the surgical operation are considered. The obtained control results to emulate the multi-phase control law used in practice.